Molecular advances in transfusion medicine: a narrative review - Arishi, Wjdan A.; Yaqinuddin, Ahmed; Sajid, Muhammad Raihan (Frontiers in Medicine, 2025)
This narrative review reports recent advances in transfusion medicine, encompassing enhancements in molecular diagnostics, blood engineering, and therapeutic technologies. It summarizes findings from peer-reviewed studies relevant to these emerging areas. Molecular diagnostics have evolved from low-throughput polymerase chain reaction (PCR) -based methods with specificity for known polymorphisms to high-throughput approaches, such as microarray-based genotyping and next-generation sequencing, which enable the detection of both established and novel blood group variants. In addition, the integration of genomic data with serological testing has improved the accuracy of blood group profiling and enhanced donor screening for rare antigens. Advances in blood engineering are demonstrated by studies employing induced pluripotent stem cell reprogramming and clustered regularly interspaced short palindromic repeats (CRISPR)-mediated gene editing to produce red blood cells engineered for multiple rare or null antigen phenotypes. Other investigations describe noninvasive fetal RHD genotyping (Rhesus D antigen gene genotyping), recombinant DNA technologies for standardized reagents, and gene therapy approaches that extend clinical applications beyond diagnosis to treatment. Collectively, this review demonstrates that a diversified use of molecular, genomic, and cellular technologies is reshaping antigen matching and therapeutic strategies in transfusion medicine.